Proteomic profiling of FBXW7‐mutant serous endometrial cancer cells reveals upregulation of PADI2, a potential therapeutic target - Urick, Mary Ellen (Cancer Med, 2020)
BACKGROUND: Despite advancements over the past decade revealing molecular aberrations characteristic of endometrial cancer (EC) subtypes, serous ECs remain difficult to treat and associated with poor outcomes. This is due, in part, to the rarity of these tumors within clinical trials and the inability to directly target the most frequent genomic abnormalities. One of the most commonly somatically mutated genes in serous ECs is the tumor suppressor F‐box and WD repeat domain containing 7 (FBXW7). METHODS: To identify changes in protein expression associated with FBXW7 mutation, we clustered regularly interspaced short palindromic repeats (CRISPR)‐edited ARK4 FBXW7 nonmutant serous EC cells to insert recurrent FBXW7 mutations. We then compared the liquid chromatography tandem mass spectrometry‐based proteomic profiles of CRISPR‐edited ARK1 and ARK4 serous EC cells to matched parental cells. RESULTS: Among distinct total and phosphorylated proteins that were significantly differentially expressed in FBXW7‐mutant cell lines compared to matched parental lines, we identified increased PADI2 (peptidyl arginine deiminase 2) expression in all ARK1 and ARK4 CRISPR‐edited FBXW7‐mutant cell lines. We further confirmed the correlation between FBXW7 mutation and increased PADI2 expression in a third biological background, JHUEM‐1 endometrioid EC cells. Finally, we established that PADI2 protein is expressed in primary serous endometrial tumors. CONCLUSION: Our findings provide novel insight into proteomic changes associated with FBXW7 mutation in serous ECs and identify PADI2 as a novel potential therapeutic target for these tumors.